Coffee drinks an illustrated infographic guide to what's in your cup - Jobst, Merlin
Do you know your Cappuccino from your Cortado or your Americano from your Affogato? When you are bleary-eyed at the counter of the coffee shop, faced with a menu of drinks as long as the queue of people eagerly waiting for that morning blast of caffeine, the minutiae and mechanics of coffee can be a little mind-bending. With this simple infographic guide that clearly explains the composition of all the main types of coffee drinks available, you'll be able to identify what you are sipping and just how you like it, making this an essential addition to the collection for anyone who's addicted to great coffee.